Peran guru PJOK dalam pembentukan karakter siswa - Latif, Ikhsan Al; Kurniawan, Rama; Sari, Zihan Novita (Universitas Hamzanwadi, 2023)
The phenomenon of cases of irregularities that have occurred recently has been carried out by a student or teacher, especially at school. Character education in schools is a good solution. This study aims to examine how the role of PJOK teachers plays in the formation of student character. The subjects of this study consisted of 12 PJOK teachers, 8 school principals, and 100 students who were taken using the simple random sampling technique and had been calculated using the slovin formula from a total of 4537 students. Data collection in this study used the source triangulation method with a closed questionnaire containing positive and negative question items. Data analysis used quantitative descriptive analysis in which the data processing was percentaged. The results of the data analysis show that the role of PJOK teachers is mostly in the medium category with a percentage of 57%, 27% in the low category, and 16% in the high category. These results were obtained from the role of PJOK teachers as inspiration, role models, motivators, dynamists, evaluators, leaders, facilitators, and supervisors. In conclusion, the role of PJOK teachers in building student character is still not maximal in shaping the character of their students by instilling character education values in them.